TremorFlash: Earthquake warning and follow-up system - Koirala, Aashish Dutta; Joshi, Amit Krishna; Dahal, Biswa; Joshi, Girish Bilas (Nepalese Journal of Engineering, 2005)
This paper describes the design approach towards the construction of an earthquake warning and follow-up system, TremorFlash. The approach consists in integration of software engineering and hardware organization. On software front, we utilize Unified Modeling Language specifications and tools of object-oriented analysis and design. Starting from requirements analysis using Use Case model, different tasks such as static modeling, behavioral modeling, implementation modeling and environment modeling is carried out. The hardware is assembled using locally available piece meal components. Extra effort has been applied to make TremorFlash a reliable, safe and fault-tolerant system. For this, careful hazards and risk analysis is performed along with system dependability analysis in order to map out all risks involved with the system. Furthermore, a unique application instance redundancy technique is devised for fault tolerance. Keywords: TremorFlash, core system, user module, fault-tolerant system. Nepalese Journal of Engineering Vol.1(1) 2005 pp.3-9